2018
DOI: 10.3892/ol.2018.8784
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA AFAP1‑AS1 is upregulated in NSCLC and associated with lymph node metastasis and poor prognosis

Abstract: Long noncoding RNA (lncRNA) has been indicated to have an important role in various types of malignant tumors; however, only a small number of lncRNAs have been entirely elucidated. In the present study, a novel lncRNA, actin filament associated protein 1 antisense RNA 1 (AFAP1-AS1), was investigated, which is highly expressed in non-small cell lung cancer (NSCLC). Reverse transcription-quantitative polymerase chain reaction and in situ hybridization were performed to detect AFAP1-AS1 expression in frozen tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…AFAP1-AS1 expression is positively correlated with tumor pathological grade, TNM staging, smoking history, infiltration degree, distant metastasis, and clinical outcomes in NSCLC patients [91,99,100,101]. High expression of AFAP1-AS1 is correlated with advanced lymph node metastasis and reduced survival time [102]. A meta-analysis report showed that increased expression level of AFAP1-AS1 is a strong predictor of poor OS in NSCLC patients [91].…”
Section: Lncrnas In Lung Cancer (Lc)mentioning
confidence: 99%
See 1 more Smart Citation
“…AFAP1-AS1 expression is positively correlated with tumor pathological grade, TNM staging, smoking history, infiltration degree, distant metastasis, and clinical outcomes in NSCLC patients [91,99,100,101]. High expression of AFAP1-AS1 is correlated with advanced lymph node metastasis and reduced survival time [102]. A meta-analysis report showed that increased expression level of AFAP1-AS1 is a strong predictor of poor OS in NSCLC patients [91].…”
Section: Lncrnas In Lung Cancer (Lc)mentioning
confidence: 99%
“…AFAP1-AS1 is upregulated in NSCLC tissues and cell lines [91,99,100,101,102,103,104,105,106,107]. Inhibition of AFAP-AS1 suppresses cell growth and migration and promotes apoptosis of NSCLC cells in vitro [103,104].…”
Section: Lncrnas In Lung Cancer (Lc)mentioning
confidence: 99%
“…Long non‐coding RNAs (lncRNAs) have been demonstrated to play essential role in the development of malignant tumors . They were suggested to involve in various biological modifications including epigenetic modification and transcriptional/post‐transcriptional regulation .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous previous studies have illuminated that noncoding RNAs (ncRNAs), such as long non-coding RNAs (LncRNAs), microRNAs (miRNAs), small nucleolar RNAs (snoRNAs), are emerging as a critical regulator or key elements of cell proliferation and metastasis in human non-small-cell lung cancer (Ji et al 2003;Liao et al 2010;Tang et al 2017). Over the past decades, multiple LncRNAs (defined as > 200 nucleotides in length) have been annotated and identified key roles in cell cycle and regulating gene expression in cancers (Gutschner and Diederichs 2012;Spizzo et al 2012;Shi et al 2013), such as LncRNA HOTAIR (Gupta et al 2010), LncRNA MALAT-1 (Ji et al 2003), LncRNA AFAP1-AS1 (Leng et al 2018), LncRNA NEAT1 (Sun et al 2016), LncRNA TUG1 (Zhang et al 2014). Furthermore, a comprehensive assessment suggested that the dysregulation of lncRNAs has increasingly become an endogenous force in the formation of human cancers (Shi et al 2013;Leng et al 2018).…”
Section: Introductionmentioning
confidence: 99%